Trial of Endovascular Therapy for Acute Ischemic Stroke with Large Infarct - Huo, Xiaochuan; Ma, Gaoting; Tong, Xu; Zhang, Xuelei; Pan, Yuesong; Nguyen, Thanh N.; Yuan, Guangxiong; Han, Hongxing; Chen, Wenhuo; Wei, Ming; Zhang, Jiangang; Zhou, Zhiming; et al. (The New England journal of medicine, 2023)
In a trial conducted in China, patients with large cerebral infarctions as determined by imaging criteria within 24 hours after onset had better outcomes with endovascular therapy than with medical therapy alone.